2006
DOI: 10.1111/j.1442-200x.2006.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating thein vitroeffect of taurine on the infant lymphocytes by sister chromatid exchange

Abstract: The results indicated that taurine plays a protective role in MMC-induced sister chromatid exchange in human lymphocytes. The authors suggest that the high levels of taurine found in human milk may induce protecting effects from breast-feeding against DNA damage and malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that taurine exhibits a protective effect against cellular-stress induced oxidation [ 8 , 14 ]. Indeed, taurine behaves as a free radical scavenger in various cells and tissues [ 9 - 11 , 14 ]. The protective effects of taurine against cytotoxicity and oxidative stress have been observed in cells and tissues, both in vivo and in vitro [ 8 , 9 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that taurine exhibits a protective effect against cellular-stress induced oxidation [ 8 , 14 ]. Indeed, taurine behaves as a free radical scavenger in various cells and tissues [ 9 - 11 , 14 ]. The protective effects of taurine against cytotoxicity and oxidative stress have been observed in cells and tissues, both in vivo and in vitro [ 8 , 9 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, taurine behaves as a free radical scavenger in various cells and tissues [ 9 - 11 , 14 ]. The protective effects of taurine against cytotoxicity and oxidative stress have been observed in cells and tissues, both in vivo and in vitro [ 8 , 9 , 11 , 14 ]. Since we think that cytotoxic oxygen metabolites are important in the mechanism of RPE, we aimed to investigate the possible beneficial protective effects of taurine in RPE in rats.…”
Section: Introductionmentioning
confidence: 99%